DETERMINATION OF THE SECOND CRITICAL END POINT IN SILICATE-H2O SYSTEMS USING HIGH-PRESSURE AND HIGH-TEMPERATURE X-RAY RADIOGRAPHY - Mibe K.; Kanzaki M.; Kawamoto T.; Matsukage K.N.; Fei Y.; Ono S. (My University, 2004)
To determine the second critical end point in silicate-H2O systems, a new method for the direct observations of immiscible fluids has been developed using a synchrotron X-ray radiography technique. High-pressure and high-temperature experiments were carried out with a Kawai-type, double-stage, multi-anvil high-pressure apparatus (SPEED-1500) installed at BL04B1, SPring-8, Japan. The Sr-plagioclase (SrAl2Si2O8)-H2O system was used as an illustrative example. A new sample container composed of a metal (Pt) tube with a pair of lids, made of single crystal diamonds, was used under pressures between 3.0 and 4.3 GPa, and temperatures up to ∼1600°C. The sample in the container could be directly observed through the diamond lids with X-ray radiography. At around 980 to 1060°C and pressures between 3.0 and 4.0 GPa, light gray spherical bubbles moving upward through the dark gray matrix were observed. The light gray spheres that absorb less X-rays represent an aqueous fluid, whereas the dark gray matrix represents a silicate melt. These two immiscible phases (aqueous fluid and silicate melt) were observed up to 4.0 GPa. At 4.3 GPa, no bubbles were observed. These observations suggest that the second critical end point in the Sr-plagioclase-H2O system occurs at around 4.2 ± 0.2 GPa and 1020 ± 50°C. Our new technique can be applied to the direct observations of various systems with two coexisting fluids under deep mantle conditions.